Shellac dan Gelatin untuk Konsolidasi Artefak Kayu - Leliek Agung Haldoko (Balai Konservasi Borobudur Magelang, 2021)
Wood is a hygroscopic organic material, prone to damage and weathering, especially by humidity. The moisture in the wood will trigger biotic activities such as fungus, which can decompose of wood materials, that is, cellulose. Moreover, wood is susceptible to insect attacks such as termites. This condition will cause the wood to become brittle so that the strength of the wood will decrease. To strengthen brittle wood, consolidation treatments are needed. Material for wood consolidation that has been used is Paraloid B72 with acetone solvent, which is not easy to find everywhere Materials tested for wood artifacts consolidations were shellac and gelatin with a concentration of 5%, 7,5%, and 10%. As a comparison, the material used for wood consolidation is Paraloid B72 10%. Test parameters used include SEM test, density test, compressive strength test, color change test, fungal growth observation, and FTIR test. Test results have shown that shellac 7,5% and 10% can be an alternative to Paraloid B72 as a wood artifacts consolidation material. Shellac 7,5% is the optimum concentration for wood artifacts consolidation because materials will be more efficient. This material can fill the wood pores and increase the density by 13,89%. The resulting compressive strength value reached 248,01 kg/cm2 or increased by 43,18%, higher than Paraloid B72 10%. Shellac 7,5% does not change the color of the wood and safe from fungal growth when applied to wood. This material also does not change the chemical composition of wood. Keywords: wood, artifact, consolidation, shellac, gelatin, Paraloid B72